A new species of Fredlanea Martins and Galileo, 1996 from Peruvian Andes (Coleoptera: Cerambycidae, Lamiinae, Hemilophini) - Juarez-Noé, Gino; Gonzalez-Coronado, Uzbekia (Fragmenta entomologica, 2020)
A new species of genus Fredlanea Martins and Galileo, 1996 is described from Peru: Fredlanea wilderi sp. nov., based on a specimen collected from the Cuyas cloud forest in Piura region, important mountain rainforest of Peruvian Andes. The new taxon is closely related to Fredlanea guaranitica (Lane, 1966) but can be distinguished by presence of yellowish pubescence on proepisterna, mesepimera and metepisterna, and absence of longitudinal strip of yellow pubescence on epipleural margins. A key to Peruvian species of Fredlanea Martins and Galileo, 1996 is provided.